Miscellaneous

Misc 1

Misc 2

Misc 3

Misc 4

Misc 5 Important

Misc 6 Important

Misc 7 Important

Misc 8

Misc 9 Important

Misc 10

Misc 11 Important

Misc 12

Misc 13 Important

Misc 14 Important

Misc 15 Important

Misc 16 Important

Misc 17 Important

Misc 18

Misc 19

Misc 20

Misc 21 You are here

Misc 22 Important

Question 1 Important Deleted for CBSE Board 2024 Exams

Last updated at April 16, 2024 by Teachoo

Misc 21 (Method 1) If 𝑦 = |█( 𝑓(𝑥) 𝑔(𝑥) ℎ(𝑥)@𝑙 𝑚 𝑛@𝑎 𝑏 Here 𝑑𝑦/𝑑𝑥 = |█( 𝑓′(𝑥) 𝑔′(𝑥) ℎ′(𝑥)@𝑙 𝑚 𝑛@𝑎 𝑏 𝑐 )| Expanding determinant 𝑑𝑦/𝑑𝑥 = |𝑓′(𝑥)| |■8(𝑚&𝑛@𝑏&𝑐)||−𝑔′(𝑥) | |■8(𝑙&𝑛@𝑎&𝑐)||1+ ℎ′(𝑥) ||■8(𝑙&𝑚@𝑎&𝑏)| 𝑑𝑦/𝑑𝑥 = 𝑓′(𝑥) (𝑚𝑐 −𝑏𝑛)−𝑔′(𝑛) (𝑙𝑐−𝑎𝑛) + ℎ′(𝑛) (𝑙𝑏−𝑎𝑚) 𝑑𝑦/𝑑𝑥 = (𝑚𝑐 −𝑏𝑛) 𝑓′(𝑥)−(𝑙𝑐−𝑎𝑛)𝑔′(𝑥) +(𝑙𝑏−𝑎𝑚) ℎ′(𝑥) Hence We need to prove that 𝒅𝒚/𝒅𝒙 = (𝑚𝑐 −𝑏𝑛) 𝑓′(𝑥)−(𝑙𝑐−𝑎𝑛)𝑔′(𝑥) +(𝑙𝑏−𝑎𝑚) ℎ′(𝑥) Now, 𝑦 = |█( 𝑓(𝑥) 𝑔(𝑥) ℎ(𝑥)@𝑙 𝑚 𝑛@𝑎 𝑏 𝑐 )| Expanding determinant 𝑦 = 𝑓(𝑥)|■8(𝑚&𝑛@𝑏&𝑐)|− 𝑔(𝑥)|■8(𝑙&𝑛@𝑎&𝑐)|+ ℎ(𝑥)|■8(𝑙&𝑚@𝑎&𝑏)| 𝑦 = 𝑓(𝑥) (𝑚𝑐 −𝑏𝑛)−𝑔(𝑛) (𝑙𝑐−𝑎𝑛) + ℎ(𝑛) (𝑙𝑏−𝑎𝑚) 𝑦 = (𝑚𝑐 −𝑏𝑛) 𝑓(𝑥)−(𝑙𝑐−𝑎𝑛)𝑔(𝑥)" +" (𝑙𝑏−𝑎𝑚) ℎ(𝑥)" " Differentiating 𝑤.𝑟.𝑡.𝑥. 𝑑𝑦/𝑑𝑥 = 𝑑((𝑚𝑐 − 𝑏𝑛) 𝑓(𝑥) − (𝑙𝑐 − 𝑎𝑛)𝑔(𝑥)" +" (𝑙𝑏 − 𝑎𝑚) ℎ(𝑥)" " )/𝑑𝑥 𝑑𝑦/𝑑𝑥 = 𝑑((𝑚𝑐 − 𝑏𝑛) 𝑓(𝑥))/𝑑𝑥 − 𝑑((𝑙𝑐 − 𝑎𝑛)𝑔(𝑥))/𝑑𝑥 + 𝑑((𝑙𝑏 − 𝑎𝑚) ℎ(𝑥))/𝑑𝑥 𝑑𝑦/𝑑𝑥 = (𝑚𝑐−𝑏𝑛) 𝑑(𝑓(𝑥))/𝑑𝑥 − (𝑙𝑐−𝑎𝑛) 𝑑(𝑔(𝑥))/𝑑𝑥 + (𝑙𝑏−𝑎𝑚) 𝑑(ℎ(𝑥))/𝑑𝑥 𝑑𝑦/𝑑𝑥 = (𝑚𝑐−𝑏𝑛) 𝑓′(𝑥)−(𝑙𝑐−𝑎𝑛) 𝑔′(𝑥) + (𝑙𝑏−𝑎𝑚) ℎ′(𝑥)" " Hence proved Misc 21 (Method 2) If 𝑦 = |█( 𝑓(𝑥) 𝑔(𝑥) ℎ(𝑥)@𝑙 𝑚 𝑛@𝑎 𝑏 𝑐 )| , prove that 𝑑𝑦/𝑑𝑥 = |█( 𝑓′(𝑥) 𝑔′(𝑥) ℎ′(𝑥)@𝑙 𝑚 𝑛@𝑎 𝑏 𝑐 )| To Differentiate a determinant, We differentiate one row (or one column) at a time keeping others unchanged If 𝑦 = |█( 𝑓(𝑥) 𝑔(𝑥) ℎ(𝑥)@𝑙 𝑚 𝑛@𝑎 𝑏 𝑐 )| 𝑑𝑦/𝑑𝑥 = |█( 𝑓′(𝑥) 𝑔′(𝑥) ℎ′(𝑥)@𝑙 𝑚 𝑛@𝑎 𝑏 𝑐 )| + |█(𝑓(𝑥) 𝑔(𝑥) ℎ(𝑥)@(𝑙)^′ (𝑚)^′ (𝑛)^′@𝑎 𝑏 𝑐 )| + |█( 𝑓(𝑥) 𝑔(𝑥) ℎ(𝑥)@𝑙 𝑚 𝑛@(𝑎)′ (𝑏)′ (𝑐)′ )| 𝑑𝑦/𝑑𝑥 = |█( 𝑓′(𝑥) 𝑔′(𝑥) ℎ′(𝑥)@𝑙 𝑚 𝑛@𝑎 𝑏 𝑐 )| + |█(𝑓(𝑥) 𝑔(𝑥) ℎ(𝑥)@0 0 0 @𝑎 𝑏 𝑐 )| + |█( 𝑓(𝑥) 𝑔(𝑥) ℎ(𝑥)@𝑙 𝑚 𝑛@0 0 0 )| 𝑑𝑦/𝑑𝑥 = |█( 𝑓′(𝑥) 𝑔′(𝑥) ℎ′(𝑥)@𝑙 𝑚 𝑛@𝑎 𝑏 𝑐 )| + 0 + 0 𝑑𝑦/𝑑𝑥 = |█( 𝑓′(𝑥) 𝑔′(𝑥) ℎ′(𝑥)@𝑙 𝑚 𝑛@𝑎 𝑏 𝑐 )| Hence proved. Using property If any one Row or column is 0 , then value of determinate is also 0 𝑐 )| , prove that 𝑑𝑦/𝑑𝑥 = |█( 𝑓′(𝑥) 𝑔′(𝑥) ℎ′(𝑥)@𝑙 𝑚 𝑛@𝑎 𝑏 𝑐 )|